Optimization of the GDP Equation: Optimization of the GDP Equation - Cusack, Paul T E (Asian Journal of Mathematical Sciences(AJMS), 2018)
Economics are now using Engineering Mechanics to solve Economic problems. In this paper, we use Astrotheology Mathematics to optimize the GDP equation. This Econphyscis can be used to program a computer to create a real-time computer program to solve unknown variable, such as consumption, in the broad economy.